Ta2O5/ Al2O3/ SiO2 - antireflective coating for non-planar optical surfaces by atomic layer deposition - Pfeiffer, K.; Schulz, Ulrike; Tunnermann, Andreas; Szeghalmi, Adriana (Proceedings of SPIE - The International Society for Optical Engineering, 2017)
Antireflective coatings are essential to improve transmittance of optical elements. Most research and development of AR coatings has been reported on a wide variety of plane optical surfaces; however, antireflection is also necessary on nonplanar optical surfaces. Physical vapor deposition (PVD), a common method for optical coatings, often results in thickness gradients on strongly curved surfaces, leading to a failure of the desired optical function. In this work, optical thin films of tantalum pentoxide, aluminum oxide and silicon dioxide were prepared by atomic layer deposition (ALD), which is based on self-limiting surface reactions. The results demonstrate that ALD optical layers can be deposited on both vertical and horizontal substrate surfaces with uniform thicknesses and the same optical properties. A Ta2O5/Al2O3/ SiO2multilayer AR coating (400-700 nm) was successfully applied to a curved aspheric glass lens with a diameter of 50 mm and a center thickness of 25 mm.
CRIS-Team Scopus Importer:2023-04-20
Keywords: aluminum oxide; antireflection coating; Atomic layer deposition; highly curved lens; non-planar surfaces; optical coatings; silicon dioxide; tantalum oxide